2014
DOI: 10.1167/iovs.13-13562
|View full text |Cite
|
Sign up to set email alerts
|

Pathologic Alterations of the Outer Retina in Streptozotocin-Induced Diabetes

Abstract: Degenerative changes of photoreceptors and pigment epithelium shown here prior to apoptotic loss of photoreceptors may contribute to functional alterations reported in diabetic human patients and different animal models, thus may serve as a potential model for testing the efficacy of neuroprotective agents in diabetes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
67
3

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 67 publications
(91 citation statements)
references
References 55 publications
18
67
3
Order By: Relevance
“…Thus, it is more likely that the cones are present but are physiologically disturbed in a way that impairs the wave guide function of the outer segments. The LDCR in this study were seen as very distinct localized changes that did not grossly impact vision, although functional impairment and changes in metabolism of the cones may have been more widespread and could be related to cone defects that have been reported in diabetics 23,56,57 and may be related to functional changes in diabetes, 2732 which are consistent with the treatment of diabetes as a neurodegenerative disorder. 14 …”
Section: Discussionsupporting
confidence: 79%
“…Thus, it is more likely that the cones are present but are physiologically disturbed in a way that impairs the wave guide function of the outer segments. The LDCR in this study were seen as very distinct localized changes that did not grossly impact vision, although functional impairment and changes in metabolism of the cones may have been more widespread and could be related to cone defects that have been reported in diabetics 23,56,57 and may be related to functional changes in diabetes, 2732 which are consistent with the treatment of diabetes as a neurodegenerative disorder. 14 …”
Section: Discussionsupporting
confidence: 79%
“…Diabetes has also been reported to cause a reduction in the length of the rod outer segments in male Sprague–Dawley rats over a study duration of 24 weeks. Morphological signs of degeneration in the outer segments of rods, most M‐cones and some S‐cones has been reported in Male Wistar and Sprague–Dawley rats killed 12 weeks after the induction of diabetes.…”
Section: Morphological Changes To Photoreceptors Retinal Pigment Epimentioning
confidence: 98%
“…Not all studies show photoreceptor death in diabetes. Studies of male Wistar and Sprague–Dawley rats diabetic for 12 weeks reported that retinal thickness, the number of apoptotic cells, and the density of cones expressing middle (M)‐ and shortwave (S)‐sensitive opsins were similar in diabetic and control retinas. In male C57BL/6J mice diabetic for 2 months, no significant difference in the number of layers in the outer nuclear layer was detected.…”
Section: Morphological Changes To Photoreceptors Retinal Pigment Epimentioning
confidence: 99%
“…Interestingly, the foveal cones appear to be mostly affected revealing a loss of approximately 30% of the M-cones 7 weeks after type 2 diabetes was induced in the animals [46]. Studies in rats also have shown alterations in the photoreceptor outer segments with the S-cones and the M-cones most severely affected [47].…”
Section: Outcomes Of Irbp's Decreased Levels In Diabetesmentioning
confidence: 99%